SUBLIMATION OF YOUTH CHARACTER EDUCATION THROUGH RELIGIOUS CONTENT IN PAMATANG SIDAMANIK NAGORI SIMALUNGUN DISTRICT - Hidayanti, Nur; Nasution, Syawaluddin (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study aims to explore sublimation of adolescent character education through religious content . This research is descriptive research with a qualitative approach that utilises interviews, observation, and documentation. The subjects in this research are teenagers in Nagori Pamatang Sidamanik who sublimate character education and follow religious content. The data analysis technique refers to the concept of the Miles and Huberman model, namely the interactive model. The results of this study are This study found that there was a sublimation of adolescent character education through religious content through three stages, namely: primitive id encouragement, da'wah content as a super ego shaper and desire diversion into positive things. And this study found that there are three benefits of sublimation of adolescent character education through religious content including preventing or relieving anxiety, producing creative activities and full self-acceptance.